Strategi Diseminasi Dinas Komunikasi Dan Informatika (DISKOMINFO) Dalam Meningkatkan Pelayanan Informasi Kepada Masyarakat Di Kabupaten Ciamis - Regina Maharani; Yulia Citra Rahayu; Devi Karina Seviani; Muhammad Yudia Noor Akbari (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2023)
The purpose of this writing is to analyze and evaluate the dissemination strategy carried out by the Communication and Information Service (DISKOMINFO) in improving information services to the people in Ciamis Regency. This research was conducted with the aim of improving and increasing the effectiveness of existing dissemination strategies and providing recommendations for further improvement. The method used in this study was data collection through observation, interviews with Diskominfo staff, and analysis of related documentation. the research results show that in improving information services to the public, Diskominfo needs to adopt an effective dissemination strategy. By building a reliable communication infrastructure, utilizing social media and digital platforms, establishing partnerships and collaborations, and increasing digital literacy, Diskominfo can be more effective in conveying information to the public. With the right strategy, Diskominfo can achieve their goal of providing quality and equitable information services to the public.